(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, the process of formation of the Kyrgyz people is very complex and lasted more than two thousand years. Although it has gone through a difficult historical path since its formation as an ethnic group, it has retained its characteristics as a nation. and today has become an independent sovereign state with its own culture and spiritual wealth. By characteristics we mean the history, language, religion and customs of that nation. The Kyrgyz people differ from other nations with their rich cultural heritage and unique traditions. Our ancestors have long created folk traditions, customs and rituals that expressed their ideas about life and worldview. It is currently influenced by certain political views and is undergoing many changes and updates.